Prevalence trend and burden of foodborne trematodiasis in China from 1990 to 2021 and its predictions until 2030: a comparative study with Japan and South Korea - Ma, Runzhou; Li, Na; Chen, Chengming; Lan, Jianqiang; Guo, Huaibin; Zhang, Wanxing (Frontiers in Public Health, 2025)
BackgroundFoodborne trematodiasis (FBT) poses a significant public health challenge in East Asia, influenced by local dietary practices and environmental conditions. This study evaluates the prevalence trends and disease burden of FBT in China, Japan, and South Korea from 1990 to 2021, with future burden projections until 2030, to guide targeted prevention strategies and public health resource allocation.MethodsThe study utilized data from the Global Burden of Disease (GBD) 2021, including the absolute prevalence, age-standardized prevalence rate (ASPR), disability-adjusted life years (DALYs), and age-standardized DALY rate (ASDALR). Joinpoint regression analyzed the average annual percentage change (AAPC) and 95% confidence intervals (CI) to track FBT burden trends. A comparative analysis was conducted across different dimensions of the burden of FBT among China, Japan, and South Korea, including age, gender, and temporal trends. Additionally, the Bayesian age-period-cohort (BAPC) model projected future FBT burden trends.ResultsFrom 1990 to 2021, China showed significant reductions in ASPR (41.65%) and ASDALR (47.44%) of FBT. South Korea also noted a slight decrease, yet both had higher rates than the global average. Japan, conversely, saw a notable increase in FBT burden but with an overall lower burden compared to the global average. Males generally exhibited a higher disease burden than females. Future projections indicate a continued decline or stabilization in China and Japan, with a potential slight increase in South Korea by 2030.ConclusionThe study reveals contrasting trends in FBT burden among the three East Asian countries, with significant declines in China, a slight decrease in South Korea despite higher-than-global rates, and an increasing but low burden in Japan. These insights are crucial for tailoring public health interventions and allocating resources effectively to combat FBT in the region.